Genomic epidemiology of extended-spectrum beta-lactamase-producing Escherichia coli from humans and a river in Aotearoa New Zealand. - Gray HA; Biggs PJ; Midwinter AC; Rogers LE; Fayaz A; Akhter RN; Burgess SA (Microbiology Society, 2025)
In Aotearoa New Zealand, urinary tract infections in humans are commonly caused by extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli. This group of antimicrobial-resistant bacteria are often multidrug resistant. However, there is limited information on ESBL-producing E. coli found in the environment and their link with human clinical isolates. In this study, we examined the genetic relationship between environmental and human clinical ESBL-producing E. coli and isolates collected in parallel within the same area over 14 months. Environmental samples were collected from treated effluent, stormwater and multiple locations along an Aotearoa New Zealand river. Treated effluent, stormwater and river water sourced downstream of the treated effluent outlet were the main samples that were positive for ESBL-producing E. coli (7/14 samples, 50.0%; 3/6 samples, 50%; and 15/28 samples, 54%, respectively). Whole-genome sequence comparison was carried out on 307 human clinical and 45 environmental ESBL-producing E. coli isolates. Sequence type 131 was dominant for both clinical (147/307, 47.9%) and environmental isolates (11/45, 24.4%). Only one ESBL gene was detected in each isolate. Among the clinical isolates, the most prevalent ESBL genes were bla CTX-M-27 (134/307, 43.6%) and bla CTX-M-15 (134/307, 43.6%). Among the environmental isolates, bla CTX-M-15 (28/45, 62.2%) was the most prevalent gene. A core SNP analysis of these isolates suggested that some strains were shared between humans and the local river. These results highlight the importance of understanding different transmission pathways for the spread of ESBL-producing E. coli.
Keywords: E. coli; ESBL; antimicrobial resistance; freshwater; urinary tract infection; Humans; Escherichia coli; beta-Lactamases; New Zealand; Rivers; Escherichia coli Infections; Whole Genome Sequencing; Urinary Tract Infections; Drug Resistance, Multiple, Bacterial